Management of Economic Potential in Improving Family Welfare in Papua - Kambu, Arius (Majalah Ilmiah Bijak, 2025)
The research results show that building a family economy in Papua requires a holistic approach that considers local characteristics, involves community-based empowerment, and is supported by the collaboration of various parties. The main strategies include developing a sustainable agricultural sector, access to education and training based on local wisdom, and strengthening the role of women in the family economy. In addition, creative industries and tourism also hold great potential to be developed, supported by adequate infrastructure and microfinance services. The use of local technology and innovation, as well as improving financial literacy, are important steps to improve productivity and family economic management. With synergy between the government, communities and NGOs, families in Papua can overcome socio-economic challenges and build a more prosperous life in a sustainable manner.